Застосування фреймворків SWOT, "Квітка Лотоса" та SCAMPER у стратегічному аналізі та інноваційному плануванні нового протигрибкового крему - Притула, Р. Л.; Бушуєва, Інна Володимирівна; Парченко, Володимир Володимирович; Prytula, R. L.; Bushueva, I. V.; Parchenko, V. V. (My University, 2025)
Метою роботи є здійснення всебічного інтегрованого стратегічного аналізу для розроблення та комерціалізації нового протигрибкового препарату для лікування мікозу стоп, використовуючи SWOT- аналіз, техніку «Квітка Лотоса» та фреймворк SCAMPER із подальшим створенням дієвих рекомендацій для оптимізації шляху препарату від досліджень до ринку. Патофізіологія мікозу стоп, спричиненого дерматофітами (Trichophyton rubrum, Trichophyton interdigitale), підкреслює потребу в препаратах, які протидіють імунному пригніченню та зменшують рецидиви. Як результат дослідження, можна констатувати, що новий протигрибковий лікарський засіб має унікальний механізм дії, потенційно кращий профіль безпеки та формулу, що забезпечує конкурентну перевагу на фармацевтичному ринку. SWOT-аналіз виявляє сильні сторони нового протигрибкового лікарського засобу – крему «Мікозахист плюс актив» (нова формула, зручність використання, цілеспрямована дія), слабкі сторони (високі витрати, ризик резистентності), можливості (зростання ринку, експорт) та загрози (регуляторні обмеження, конкуренція генериків). Техніка «Квітка Лотоса» генерує ідеї для поліпшення прихильності пацієнтів, розширення ринкових ніш і зниження витрат, тоді як SCAMPER пропонує конкретні вдосконалення: заміну компонентів, комбінацію з іншими речовинами, адаптацію для різних груп, модифікацію форми чи дозування, використання для профілактики, усунення алергенів і зміну способів застосування. Рекомендації включають капіталізацію наукових переваг через ретельні клінічні випробування, вирішення проблем резистентності, оптимізацію зручності для пацієнтів, використання ринкових можливостей, управління витратами через партнерства тощо. Інтегрований підхід забезпечує науковий і комерційний успіх, вирішуючи незадоволені медико-фармацевтичні потреби. Foot mycosis, known as the «Athlete foot» is one of the most common fungal skin lesions, which is a significant health problem, affecting about 3% of the world’s population. Historically, the mycosis of the feet is widespread in military conditions due to humidity, unsanitary and prolonged wearing of closed shoes, which contributes to its spread of up to 43% among servicemen. In tropical climates, fungal infections account for up to 75% of skin diseases in this group. Despite the presence of local and oral antifungal agents, increasing prevalence, frequent relapses and medication resistance indicate dissatisfied needs for effective therapy. This creates a commercial incentive for the development of a new antifungal agent. The purpose of the work is to conduct a comprehensive integrated strategic analysis for the development and commercialization of a new antifungal drug for the treatment of foot mycosis, using SWOT analysis, Lotus Flower technique and Scamper Framework, followed by creating effective recommendations for optimizing the path from research to the market. The new tool has a unique mechanism of action, a potentially best safety profile and a formula that provides a competitive advantage in the pharmaceutical market. Pathophysiology of foot mycosis caused by derichophyton Rubrum (Trichophyton Interigitis), emphasizes the need for drugs that counteract immune suppression and reduce relapses. SWOT analysis reveals strengths (new formula, convenience, purposeful action), weaknesses (high costs, risks of resistance), opportunities (market growth, export) and threats (regulatory restrictions, competition of generics). Lotus Flower technique generates ideas for improving patients’ commitment, expanding market niches and reducing costs, while Scamper offers specific improvements: replacement of components, combination with other substances, adaptation for different groups, modification of shape or dosage, use for prevention, elimination. Recommendations include capitalization of scientific advantages through careful clinical trials, solving resistance problems, optimization of convenience for patients, use of market opportunities, cost management through partnerships, etc. The integrated approach provides scientific and commercial success, solving dissatisfied medical and pharmaceutical needs.
Application of SWOT, Lotus Flower and SCAMPER frameworks in strategic analysis and innovation planning of a new antifungal cream
Keywords: 1,2,4-триазол; протигрибкова активність; мікоз стоп; протигрибкові лікарські засоби; крем «Мікозахист плюс актив»; фреймворк; фармацевтична розробка; інструменти стратегічного аналізу; 1,2,4-triazole; antifungal activity; footmycosis; antifungal drugs; cream «Mycoprotection plus active»; framework; pharmaceutical development; strategic analysis tools